First record of Anopheles (Anopheles) hyrcanus (Pallas 1771) (Diptera: Culicidae) in Poland - Renke Lühken; Norbert Becker; Dagmara Dyczko; Felix G. Sauer; Konstantin Kliemke; Jonas Schmidt-Chanasit; Katarzyna Rydzanicz (Parasites & Vectors, 2023)
Abstract The spatial distribution of mosquito species in the course of globalization and climate warming is highly dynamic. Different studies have demonstrated the spread and establishment of thermophilic mosquito species, potentially increasing the prevalence of ‘nuisance’ mosquitoes and the local transmission of pathogens. Here we report the first recorded sampling of Anopheles hyrcanus in Wrocław, southwest Poland. This is the most northern detection of this species to date in Europe. Future spread and population development of this potential vector of malaria parasites, viruses or zoonotic helminths, such as Dirofilaria spp., must be monitored carefully. Potential factors underlying the spread of this species are discussed. Graphical Abstract